Phenomics Approach to Investigate Behavioral Toxicity of Environmental or Occupational Toxicants in Adult Zebrafish (Danio rerio). Issue 8 (13th August 2021) - Audira, Gilbert; Lai, Yu‐Heng; Huang, Jong‐Chin; Chen, Kelvin H.‐C.; Hsiao, Chung‐Der
Abstract: Over the last few years, environmental pollution, especially water pollution, has become a serious issue worldwide. Thus, methods that can help us understand the impact and effects of these pollutants, especially on aquatic animals, are needed. Behavioral assessment has emerged as a crucial tool in toxicology and pharmacology because many studies have shown, in multiple animal models, that various pharmacological compounds can alter behavior, with many of the findings being translatable to humans. Moreover, behavior study can also be used as a suitable indicator in the ecotoxicological risk assessment of pollutants. Several model organisms, especially rodent models, have been extensively employed for behavior studies. However, assessments using this model are generally time consuming, expensive, and require extensive facilities for housing experimental animals. Moreover, behavioral studies typically use different measurements and assessment tools, making comparisons difficult. In addition, even though behavioral phenomics has the potential to comprehensively illustrate the toxicities of chemicals, there is only a limited number of studies focusing on animal behavior using such a global approach. Here, we describe a phenomics approach that can be used to investigate the impact of pollutants using zebrafish. The approach consists of several behavioral tests, including response to a novel environment, mirror‐reflection image, predator fish, and conspecifics, after exposure to a test chemical. Phenotype fingerprinting, a method for summarizing individual phenotypes based on the results of the behavioral tests, is then conducted to reduce data complexity and display the pattern of each compound on behavioral phenotypes in zebrafish. This approach may be useful to researchers studying the potential adverse effects of different pollutants. © 2021 Wiley Periodicals LLC. Basic Protocol 1 : Novel tank test Basic Protocol 2 : Shoaling test Basic Protocol 3 : Aggression test (mirror biting test) Basic Protocol 4 : Social interaction test Basic Protocol 5 : Fear response test Basic Protocol 6 : PCA and heatmap clustering